2016
DOI: 10.1111/pde.13048
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Scrub Typhus Eschar in South Indian Children

Abstract: Careful examination for eschar in children presenting with fever, particularly in the skin folds of the groin, genitalia, and axillae, can aid in early diagnosis of scrub typhus. Lymphadenopathy should alert the clinician to the possibility of finding an eschar in the drainage area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There is a different pattern in female patients, whose anterior chest, head and neck are the most prevalent areas [ 13 , 14 ]. Eschars are also commonly present in the axillae of children in addition to the sites mentioned above [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a different pattern in female patients, whose anterior chest, head and neck are the most prevalent areas [ 13 , 14 ]. Eschars are also commonly present in the axillae of children in addition to the sites mentioned above [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Babu et al, in their prospective study found only 34.6% of serologically confirmed scrub typhus to have eschar. 10 Absence of eschar could be secondary to previous exposure to ricketssial antigen and variation in cutaneous immune response and that could be possible reason for absence of eschar in majority of our study children.…”
Section: Discussionmentioning
confidence: 78%
“…Lack of pain and hidden anatomical locations make it difficult to spot an eschar. Enlarged and tender regional lymph nodes may suggest the possibility of an occult eschar in the draining areas 4,5 …”
Section: Discussionmentioning
confidence: 99%